Emergency Care Research Funding in the Global Health Context: Trends, Priorities, and Future Directions. (December 2013) - Vu, Alexander; Duber, Herbert C.; Sasser, Scott M.; Hansoti, Bhakti; Lynch, Catherine; Khan, Ayesha; Johnson, Tara; Modi, Payal; Clattenburg, Eben J.; Hargarten, Stephen; Hauswald, Mark
Abstract Over the past few decades there has been a steady growth in funding for global health, yet generally little is known about funding for global health research. As part of the 2013 Academic Emergency Medicine consensus conference, a session was convened to discuss emergency care research funding in the global health context. Overall, the authors found a lack of evidence available to determine funding priorities or quantify current funding for acute care research in global health. This article summarizes the initial preparatory research and reports on the results of the consensus conference focused on identifying challenges and strategies to improve funding for global emergency care research. The consensus conference meeting led to the creation of near‐ and long‐term goals to strengthen global emergency care research funding and the development of important research questions. The research questions represent a consensus view of important outstanding questions that will assist emergency care researchers to better understand the current funding landscape and bring evidence to the debate on funding priorities of global health and emergency care. The four key areas of focus for researchers are: 1) quantifying funding for global health and emergency care research, 2) understanding current research funding priorities, 3) identifying barriers to emergency care research funding, and 4) using existing data to quantify the need for emergency services and acute care research. This research agenda will enable emergency health care scientists to use evidence when advocating for more funding for emergency care research.